Yield components, chemical characterization and polyphenolic profile of Tithonia diversifolia in Valle del Cauto, Cuba - Verdecia, D. M.; Herrera, R. S.; Ramírez, J. L.; Bodas, R.; Leonard, I.; Giraldéz, F. J.; Andrés, S.; Santana, A.; Méndez-Martínez, Y.; López, S. (Cuban Journal of Agricultural Science, 2018)
In order to determine the effect of regrowth age on the components of yield, chemical composition and polyphenolic profile of Tithonia diversifolia, an experiment was carried out using a randomized block design with four replications in brown soil with carbonate. The treatments consisted of three regrowth ages (60, 120 and 180 days). To establish the functional relationship between the different evaluated indicators and age, linear, quadratic, cubic and Gompertz equations were analyzed, selecting the best fit according to high value of R2, high significance of the terms and of the equation, low standard error of estimation and of terms, and significant contribution of terms and of the equation. The equations of the best fit for the functional relationship between the different evaluated indicators and age, in each seasonal period, were quadratic. There was an increase in yield of dry matter, NDF, ADF, ADL with age, with maximum values at 180 days (23.92t/ha, 47.63, 31.38 and 21.01%, respectively); edible biomass, CP, cellular content, in vitro degradability of dry matter decreased with age and the best values were obtained at 60 days (26.16 t/ha, 27.49 %, 59.56 % and 75.78 %, respectively) and the contents of total phenols, total tannins, total condensed tannins, free condensed tannins and condensed tannins bound to the fiber showed their highest values during the rainy period (12.36, 5.36, 14.55, 4.07 and 11.16 g/kgDM, respectively). The regression equations that explain the close relationship of age with yield, chemical composition and degradability were established, as well as response patterns were established for each seasonal period. It is recommended to endorse these results in other climatic and management conditions of the species. Key words: yield components, chemical composition, secondary metabolites